The Study of Subtalar Hyper-Pronation Correction by Medial Longitudinal Arch Taping, on the Knee joint Malalingment and Pain - Farzaneh Yazdani; Mohsen Razeghi; Samaneh Ebrahimi; Shohreh Taghi Zadeh (Vesnu Publications, 2014)
Introduction: In assessing the factors affecting the knee joint biomechanics foot malalingments are more important due to ability to change the applied force direction, so the main goal of this study was to investigate the relationship between the excessive subtalar pronation and changes of Q-angle and whether taping of the Medial Longitudinal Arch (MLA) could accordingly change these variables. Materials and Methods: 76 volunteers (aged 20-40 years) were recruited from physical therapy clinic of shiraz school of rehabilitation and were divided to 2 groups.  1) Pronated Symptomatic Knees (PSK) included 38 subjects having excessive subtalar pronation and knee symptoms.  2) Pronated Asymptomatic Knees (PASK), included 38 subjects having excessive subtalar pronation without knee symptoms. Subtalar and Q-angles were measured before and after medial longitudinal arch Taping by employing a goniometer in both PSK and PASK groups.  Pearson Correlation coefficient Test, Paired sample T-Test and Wilcoxon test were used to fulfill the statistical analysis. Results: A strong correlation was found between subtalar and Q-angles before taping in both  PSK & PASK groups. In females (P=0.002) and (P= 0.0010) for PSK and PASK, respectively and in males (P=0.001) and (P =0.001) for PSK and PASK, respectively. There was a significant difference between subtalar angle and Q-angles before and after applying taping method in both PSK & PASK.   Conclusion: It seems that in the hyper pronated foot subjects applying the MLA taping method may result in decreasing the Q- angle which, in turn, may eventually improve knee joint biomechanics.   Key words: Flat foot, subtalar pronation, Q angle, Taping